2020
DOI: 10.3389/fmicb.2020.01319
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Administration Routes and Oral Exposure to Antibiotic Resistant Bacteria as Key Drivers for Gut Microbiota Disruption and Resistome in Poultry

Abstract: Impact of Oral Antibiotics on Poultry due to the pre-existing bacteria that are (i) less susceptible to Amp, and/or (ii) with Amp r-or multidrug resistance-encoding genes other than bla CMY−2 +. These results demonstrated the critical interplay among drug administration routes, microbiota seeded through the gastrointestinal tract, AR, gut microbiota disruption, and the rise of common opportunistic pathogens in hosts. The potential implications in human and animal health are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 52 publications
(62 reference statements)
3
24
0
Order By: Relevance
“…While these data illustrated the profound impact of oral antibiotics on gut microbiota disruption and associated host responses, previous reports illustrated that changing ampicillin and vancomycin from oral to injective administration significantly alleviated the damages on gut microbiota (Zhang et al, 2013;Isaac et al, 2017;Zhou et al, 2020). These findings are consistent with the report by Vogt et al (2016), showing that intraperitoneally injected minocycline does not display anxiolytic or anti-depressant behaviors in mice.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…While these data illustrated the profound impact of oral antibiotics on gut microbiota disruption and associated host responses, previous reports illustrated that changing ampicillin and vancomycin from oral to injective administration significantly alleviated the damages on gut microbiota (Zhang et al, 2013;Isaac et al, 2017;Zhou et al, 2020). These findings are consistent with the report by Vogt et al (2016), showing that intraperitoneally injected minocycline does not display anxiolytic or anti-depressant behaviors in mice.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, a series of studies have highlighted that gut microbiota bidirectionally communicates with the brain and gut dysbiosis is closely associated with the occurrence of psychiatric disorders, including Alzheimer's disease (AD) (Bercik et al, 2011;Quigley, 2017;Rieder et al, 2017). The exposure of humans and animals to antibiotics, particularly oral administration, reduces bacterial diversity and induces antibiotic resistance, gut dysbiosis, and psychiatric disorders depending on the route of their administration: orally administered antibiotics such as ampicillin generally altered gut microbiota more severely than parentally injected ones (Zhang et al, 2013;Modi et al, 2014;Jang et al, 2018a;Zhou et al, 2020). Fröhlich et al (2016) reported that oral gavage of an ampicillin, vancomycin, neomycin, bacitracin, and meropenem cocktail, which did not enter the brain, disrupted gut microbiota and impaired cognitive function in a novel object recognition task.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, poultry is considered as the largest sector of the food-producing industry [ 6 ]. In addition, poultry is considered to be fed the largest amount of antibiotics and to be an important producer of animal waste, thus significantly affecting the environment and contributing to the emergence of AR and MDR bacteria [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The various antimicrobials used in poultry feed have been reported to profoundly affect the gut microbial community structure [ 12 ]. Understanding the effect of various antibiotics used commonly in the poultry feed on the gut microbiota is important as it can help in the targeted mitigation of various microbes [ 7 ]. Moreover, identifying the problematic strains associated with AMR can also help in designing AR mitigation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…However, enteral antibiotics (AB), specifically aminoglycosides, appear to reduce NEC incidence in preterm infants, 7 which is in agreement with the effects seen in experimental NEC models, 8,9 whereas prolonged intravenous AB is associated with an increased risk of NEC. 10,11 On the other hand, studies in mice and chicken show increased AB resistance after enteral relative to injected ampicillin or tetracyclin administration, 12,13 thereby limiting the use of enteral AB for NEC prophylaxis. Moreover, neonatal gut microbiota depletion by enteral AB treatment appears to hamper gut microbiota-mediated myelopoiesis and resistance to systemic infection.…”
Section: Introductionmentioning
confidence: 99%